Study on Technology and Operation Strategy of Internet TV - Jungen Su; Liu Yang; Wei Lu; Duo Shao (Dianxin kexue)
This paper introduces the development of domestic and abroad internet TV industry and analyzes the system framework and key technologies of internet TV. From the perspective of telecom operators, operating strategies and market promotion are discussed for making use of advantages of telecom resources to develop reasonable technology strategy.